2015
DOI: 10.1007/s00125-015-3725-2
|View full text |Cite
|
Sign up to set email alerts
|

Excessive gestational weight gain and gestational diabetes: importance of the first weeks of pregnancy

Abstract: Gestational diabetes mellitus (GDM) is associated with many adverse neonatal and maternal outcomes and prevention of this condition is considered a key strategy for breaking the intergenerational cycle of obesity and diabetes. Whether prevention of excessive gestational weight gain in the first weeks of pregnancy is associated with a reduced risk for GDM is currently unclear. In this issue of Diabetologia, Brunner et al (DOI: 10.1007/s00125-015-3686-5) address this possible association by conducting a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…As predicted, studies evaluating the effect of GWG on GDM has been shown risks to be both increased [23] and decreased [24] The Committee also accurately predicted that treatment for the condition would alter the pattern of weight gain after diagnosis [25, 26]. More recent studies have evaluated GWG prior to early screening and shown that early in pregnancy, increased GWG does precede the diagnosis of GWG [2729].…”
Section: Discussionmentioning
confidence: 99%
“…As predicted, studies evaluating the effect of GWG on GDM has been shown risks to be both increased [23] and decreased [24] The Committee also accurately predicted that treatment for the condition would alter the pattern of weight gain after diagnosis [25, 26]. More recent studies have evaluated GWG prior to early screening and shown that early in pregnancy, increased GWG does precede the diagnosis of GWG [2729].…”
Section: Discussionmentioning
confidence: 99%
“…The association between a higher pre-pregnancy BMI and GDM might be explained by the fact that obese women, due to greater fat deposition, have lower insulin sensitivity as compared normal weight women [56]. Prevention of GDM is considered a key strategy for breaking the intergenerational cycle of obesity and diabetes [57]. Thus, strategies aiming at preventing obesity in young women and keeping appropriate preconception weight in pre-pregnant women are essential for the prevention of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, obesity at the beginning of pregnancy has been suggested to increase the likelihood of PPD (Molyneaux et al, 2014), and PPD has been suggested to be a preface to a chronic depressive disorder (Vliegen et al, 2014). In turn, high pre-pregnancy BMI and excessive weight gain during early pregnancy are associated with a significantly increased risk of GDM (Morisset et al, 2010;Robitaille, 2015). Women with GDM are also at greater risk of developing type 2 diabetes mellitus later in life (Bellamy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%